A study of passive inverse synthetic aperture radar imaging - Shen, Bowen (2016)
This final year project studies the topic of passive inverse synthetic aperture radar imaging by using Matlab simulation. Many basic concepts about radar imaging are discussed and mathematical operations involved are also explained. Although the idea of passive Inverse Synthetic Aperture Radar (ISAR) introduces many complications compared to normal radar imaging techniques, it has many other advantages such as greater coverage and availability of signals in consumer market and its stealth characteristics. On the other hand, as passive waveform is less studied in radar imaging research compared to its active counterpart, this report uses step-by- step derivation from existing studies to achieve the final target imaging using signal with passive radar signal characteristics. There are many drawbacks of using the far less ideal passive signals for ISAR imaging, which will also be discussed.